Electrogastrography in Delayed Gastric Emptying - Badriul Hegar; Yvan Vandenplas (Indonesian Pediatric Society, 1998)
Disorders of gastric motility are generally manifested by an abnormal rate of gastric emptying. The emptying process of the stomach is very complex, and knowledge is limited to the observation that gastric emptying rate is a highly variable phenomenon, and that delayed gastric emptying is frequently the case. The advances in the knowledge of the physiology of gastric muscle and enteric nerves, and the recognition of the patterns of organization of smooth muscle contractions gave a new input to the study of gastric motility. The gastric emptying can be monitored in various ways, such as manometry, scintigraphy, or electrogastrography (EGG). Recently, EGG has received more attention. There is correlation between the EGG signal obtained from body surface electrodes and signals obtained directly from electrodes locates in the gastric muscle (serosal records). Some studies showed an association between EGG-findings and gastric motility disorders, and indicate that EGG is a reliable, non-invasive, useful method to detect gastric myoelectric activity.